The Study of Gas-Dynamic Processes in the Current Boiler Fluidized Bed; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Baturin D. A. Dmitry (2015, 2015)
Title screen